Event‐scale pebble mobility observed by RFID tracking in a pre‐Alpine stream: a field laboratory. Issue 3 (17th December 2019) - Ivanov, Vladislav; Radice, Alessio; Papini, Monica; Longoni, Laura
Abstract: Understanding coarse sediment transport is crucial for the prediction of sediment migration and the consequent development of fluvial morphologies. In this study, cobble displacements in a pre‐Alpine creek have been recorded by means of radio frequency identification (RFID). Pebble monitoring has been systematically performed after each rainfall event with moderate precipitation, in order to exclude the superimposition of sediment displacements induced by triggering factors acting at different times. The analysis of the collected data was carried out through the application of both a principal component analysis and the Buckingham Π theorem. The experimental trends were interpreted considering the ratio of mobile pebbles, the pebbles' displacement and virtual velocity as the dependent variables. These quantities mostly depend on the event peak discharge, with a nonlinear increase of the travelled distance and a growth of up to two orders of magnitude of the virtual velocity (for an approximately 10× increase in peak discharge). An inverse dependency of the virtual velocity on the event duration was also observed. A comparison of the results obtained with those from laboratory investigations of bedload transport mechanics evidenced the differences in parametric trends associated with sediment mobility in the two environments. This contrast brings forward the combination of multiple drivers of sediment mobility, such as local morphology, sediment dimensions and flow unsteadiness, warranting a further in‐depth investigation. Representation of results in a dimensionless form is suggested as a good practice to analyse data from case studies characterized by different scales. © 2019 John Wiley & Sons, Ltd. Abstract : Bed‐load pebble tracking was successfully performed in a natural creek, surveying pebble locations after each sediment mobilizing event. The sediment mobility was reasonably correlated with the peak flow rate of the events, while a dependency of pebble motions on the event duration was less clear. Dimensionless representation of the results was used as a sound basis for comparison of experimental data from different contexts.